Physiochemical Analysis of Fresh Water Sources in District Bhimber, Azad Jammu Kashmir - Iftikhar Alam; Salim Shehzad; Saqib Mehmood (International Journal of Economic and Environmental Geology, 2018)
The present study investigates the physiochemical parameters of drinking water quality in district Bhimber of Azad Jammu and Kashmir. The drinking water supplies in the area come from four main sources, streams, springs, hand pumps and boreholes. A total of seventy one (71) samples from all four water sources were taken for determination of physiochemical parameters. The results show considerable variation in water quality parameters of different water sources. However, the data analyses indicate that physiochemical parameters of water samples are well within the permissible limits of drinking water quality. Stream water samples show slightly higher pH values, while two samples from hand-pump have shown marginally higher content of TDS. The mean values of dissolved oxygen in borehole and hand-pump water samples are also slightly below the water quality standard limits. The correlation studies show that pH has a strong negative correlation with calcium and positive relation with sodium in water samples of all four sources. Similarly, the dissolved oxygen has shown negative relationship with temperature and a weak to moderate positive relationship with pH of water. No evidence of pollution and industrial contamination of water was found. The study found that water from all four sources is safe for drinking purpose.